Synthesis of β-difluoroalkyl azides via elusive 1,2-azide migration - Ning, y; Sivaguru, p; Zanoni, G; Anderson, EA; Bi, X (Elsevier, 2019)
The development of azide migration reactions is a formidable challenge because of the potential competition of side processes driven by the release of molecular nitrogen. Here, we report a conceptually novel 1,2-azide migration in an unprecedented gem-difluorination of the readily available α-vinyl azides, a transformation that enables the synthesis of a range of novel β-difluorinated alkyl azides. The practicality of the method is demonstrated by broad substrate scope, excellent functional group compatibility, and high yields. The migrating group selectivity can be tuned through electronic effects, and DFT calculations suggest 1,2-azide migration occurs via a three-membered azacyclic transition state. By using routine protocols, the β-difluorinated alkyl azide products can be easily transformed to biologically relevant β-difluorinated amines—common structural motifs in pharmaceuticals, thus demonstrating the utility of these fluorinated organic azides for pharmaceutical synthesis as well as other synthetically useful derivatives.